2019
DOI: 10.1021/acs.iecr.9b01471
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Electrochemical Ammonia Oxidation on Pt(100) from First Principles

Abstract: The electrocatalytic ammonia oxidation reaction (AOR) to molecular dinitrogen (N2) is an essential component within a sustainable nitrogen cycle. The state-of-the-art Pt nanocatalyst, preferably terminated with (100) facets, suffers from a large overpotential (>0.5 V) and rapid deactivation, the origin of which remains largely unexplained due to the intrinsic complexity of solid-electrolyte interfaces. Within the framework of grand-canonical density functional theory (GC-DFT), we show that on Pt(100) the dehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 61 publications
8
86
0
Order By: Relevance
“…First, we assume the entire route reaction network, considering the detailed binding properties of intermediate species and the corresponding limiting potentials of elementary reaction steps, and then, the most favorable pathway and RDS will be confirmed. [ 24 ] The competitive HER was also considered and compared on the MBene catalysts, and it was found that most of these MBene candidates have high selectivity for the NORR except for Ti 2 B 2 , V 2 B 2 , and Zr 2 B 2 . We also evaluated the electronic properties, studied the electron transfer processes of this new class of 2D materials for NORR and compared them with 2D MXenes.…”
Section: Introductionmentioning
confidence: 99%
“…First, we assume the entire route reaction network, considering the detailed binding properties of intermediate species and the corresponding limiting potentials of elementary reaction steps, and then, the most favorable pathway and RDS will be confirmed. [ 24 ] The competitive HER was also considered and compared on the MBene catalysts, and it was found that most of these MBene candidates have high selectivity for the NORR except for Ti 2 B 2 , V 2 B 2 , and Zr 2 B 2 . We also evaluated the electronic properties, studied the electron transfer processes of this new class of 2D materials for NORR and compared them with 2D MXenes.…”
Section: Introductionmentioning
confidence: 99%
“…The *OH species, thermodynamically stable at >0.5 V, plays a significant role in boosting kinetics via preferential stabilization of *NH through hydrogen bonding. [ 234 ] At the high operation potentials (>0.63 V vs RHE), when the *NH dehydrogenation to *N becomes thermodynamically favorable, surface deactivation occurs. However, the dimerization of *N with *N or *NH is kinetically facile, implying that the adsorbed *N is only the precursor to poisoning species (e.g., *NO) on Pt(100) surface.…”
Section: The Aor For Direct Ammonia Fuel Cellsmentioning
confidence: 99%
“…276 Also, calculations with dynamical solvent have been performed 277,278 using the blue moon ensemble 279 method. Pioneering studies have shown the importance of analyzing the kinetics at constant potential rather than constant particle number as well as demonstrated the viability of GCE-TST in computing electrocatalytic rate constants from first principles for a wide class of electrocatalytic PCET reactions such as for hydrogen evolution, 64,65,272,275 CO 2 reduction, 266,280 CO reduction, 281 NH 3 oxidation, 282 nitrogen reduction, 283 and oxygen reduction reactions, 277 for example. Yet, all these first principles studies thus far have focused on classical reactions and neglected e.g.…”
Section: Adiabatic Reactionsmentioning
confidence: 99%